City-level pathways to carbon peak and neutrality in China - Zhang, Li; Ruan, Jianhui; Zhang, Zhe; Qin, Ziyu; Lei, Zhongyi; Cai, Bofeng; Wang, Shouyang; Tang, Ling (Cell reports sustainability, 2024)
Chinese cities need independent but synergetic dual-carbon abatement roadmaps to mitigate climate change and achieve carbon neutrality. Using source-level data, we develop a time-series, full-scale emission inventory for all Chinese cities from 2005 to 2020, exploring associated heterogeneous and homogeneous patterns. We find that 31% of cities have had a significant carbon emission peak, with the main driver being carbon intensity reductions through efficiency gains and structural improvements. Despite discrepant emission levels and socioeconomic determinants, a uniform trajectory in emission changes exists across cities via four emission phases: growth of 8%–9% annually (95% confidence interval) before peaking; plateau and decline by 9%–13% for 5–7 years; and plain with slower declines. We project that if cities follow their early-peaked counterparts’ mitigation pathways, China will reach a carbon peak in 2026 at 13 Gt and carbon neutrality during 2051–2058, revealing the feasibility of Chinese climate goals and the importance of long-reaching, city-targeted planning. Science for society: China established its dual-carbon goals to achieve a carbon peak before 2030 and carbon neutrality by 2060. It is important for cities to identify their distinctive patterns and define individual dual-carbon roadmaps to achieve carbon neutrality in China. In this study, we conduct a carbon inventory for all Chinese cities from 2005 to 2020 to quantitatively define the emission phases in the process of carbon peak. We find that 31% of cities have had a significant carbon emission peak, with the main driver being carbon intensity reductions. A uniform trajectory in emission changes exists across cities, despite significant differences in emission levels and socioeconomic determinants. We project that if cities follow their early-peaked counterparts’ mitigation pathways, China could achieve its climate change goals ahead of the policy deadlines.